Understanding ‘Urf (custom) and local wisdom: an Islamic perspective - Mochammad Sahid, Mualimin; Fettane, Amar (2018)
The sources of Syariah (Islamic law) are classified into two categories; primary and secondary sources. In fiqh (Islamic jurisprudence), the classification is important for it will determine from which the ahkam (rules) of Allah are discovered, in which the dalil (guide) or source of Syariah will give weight. The majority of scholars agreed that there are four primary sources for Syariah; Quran, Sunnah, Ijma’ (scholars’ consensus) and Qiyas (analogy). The other category is the secondary sources in which the scholars differ in utilising them as a basis in deriving the ahkam. Some scholars considered them as a source, whilst others decline to utilise them in deriving the rulings of Fiqh. ‘Urf or adat (custom) is one of the Syariah secondary sources defined as the matter on which a community of people agree in the course of their daily life, or it is a common usage to refer to specific actions repeatedly performed by individuals and communities. Majority of mazahib (schools of fiqh) consider ‘urf a legal principle in respect of matters about which there is no definitive actions. They consider ‘uruf as a dalil when there is no specific nas (text) or it is contrary to any other dalil. Meanwhile, local wisdom (local knowledge) can be defined as a policy or noble values contained in the richness of the local culture in the form of traditions, manners and life motto. This paper is an attempt to explain the correlation between the two terminologies in terms of their differences and similarities related to people’s understanding when applying them in their daily life. The study will examine whether the two are the same in terms of their compliance to the Syariah and acceptable within the Islamic teachings. The study suggests that misconception on this issue must be corrected based on reliable dalil. The practices of people in their daily ibadat (devotion to God) based on current understanding must be rectified so that they can be in line with Syariah. At the end of study, it reveals that not all practices based on both ‘urf (adat) and local wisdom are islamically acceptable. There is an urgent need to reassess the practices which seem to be similar, yet they differ in many aspects.